ROLE OF MYCORRHIZAE AS BIOFERTILIZER AND BIOPROTECTANT - S.K. DWIVEDI; SANGEETA; RAM GOPAL (International Journal of Pharma and Bio Sciences, 2015)
Mycorrhizae are obligate fungi that predominate in the roots and soil of higher plants. They form association with plant roots in a host-non specific manner. Seven types of mycorrhizae have been known i.e. arbuscular, ecto, arbutoid, ectendo, ericoid, monotropoid and orchidaceous mycorrhizae. Out of these, arbuscular and ectomycorrhizae are the most abundant and wide spread. They promote plant growth by enhancing nutrient acquisition and promoting growth hormones. They also increase the resistance in plants against plant pathogens and surface area of root system for better absorption of nutrient from soil. Therefore, they can be used as biofertilizer and as biocontrol agent. This article presents an overview of current knowledge on mycorrhiza and their potential benefits to agriculture as biofertilizer and biocontrol agent.